PERANCANGAN MEDIA PEMBELAJARAN BERBASIS POWERPOINT PADA MATA PELAJARAN IPS POKOK BAHASAN KERAJAAN ISLAM KELAS X - Muliyani, Sri; Saputra, Hendra Nelva; Darman, Darman (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2025)
The teaching of Social Studies (IPS) at the senior high school (SMA/MA) level plays an essential role in developing students’ critical thinking skills and historical understanding. However, classroom practices are still largely dominated by lecture methods and the use of conventional PowerPoint presentations that lack interactivity, resulting in passive learning and difficulty in comprehending historical material. This study focuses on designing an interactive PowerPoint-based learning media for the topic Islamic Kingdoms in Indonesia for tenth-grade students, aiming to provide an engaging, communicative, and student-centered alternative suited to the characteristics of 21st-century learners. The research employs a Research and Development (R&D) method with a descriptive quantitative approach, adapting the ADDIE model but limited to the design and development stages. The study involved three subject matter experts, three media experts, and ten tenth-grade students who were introduced to the developed media. Data were collected through expert validation sheets and structured questionare, then analyzed descriptively and quantitatively. The validation results indicated that the media achieved an average feasibility score of 89%, categorized as “highly feasible.” Student questionnaire responses also showed positive perceptions toward the media’s design, ease of navigation, and clarity of content. The interactive PowerPoint media effectively stimulated students’ interest and engagement in Social Studies learning. Therefore, this study concludes that the interactive PowerPoint-based learning media is suitable to be used as an initial innovation to enhance the quality and attractiveness of Social Studies learning on Islamic history topics in tenth grade. ABSTRAKPembelajaran Ilmu Pengetahuan Sosial (IPS) di jenjang SMA/MA memiliki peran penting dalam membentuk kemampuan berpikir kritis dan pemahaman historis peserta didik. Namun, praktik pembelajaran di lapangan masih didominasi metode ceramah dan penggunaan media PowerPoint konvensional yang kurang interaktif, sehingga siswa cenderung pasif dan mengalami kesulitan memahami materi sejarah. Penelitian ini berfokus pada perancangan media pembelajaran berbasis PowerPoint interaktif pada materi Kerajaan-Kerajaan Islam di Indonesia kelas X yang bertujuan untuk menghadirkan alternatif media yang menarik, komunikatif, dan sesuai dengan karakteristik peserta didik abad ke-21. Penelitian ini menggunakan metode Research and Development (R&D) dengan pendekatan deskriptif kuantitatif yang mengadaptasi model ADDIE, namun hanya dilaksanakan hingga tahap design dan development. Subjek penelitian meliputi tiga ahli materi, tiga ahli media, dan sepuluh siswa kelas X yang diperkenalkan dengan media hasil rancangan. Data dikumpulkan melalui lembar validasi ahli dan kuesioner terstruktur, kemudian dianalisis secara deskriptif kuantitatif. Hasil validasi menunjukkan bahwa media memperoleh skor rata-rata kelayakan sebesar 89% dengan kategori “sangat layak”. Hasil kuesioner dengan siswa menunjukkan tanggapan positif terhadap aspek tampilan, kemudahan navigasi, dan kejelasan materi. Media PowerPoint interaktif ini terbukti mampu menstimulasi minat dan keterlibatan siswa dalam pembelajaran IPS. Dengan demikian, penelitian ini menyimpulkan bahwa media pembelajaran berbasis PowerPoint interaktif layak digunakan sebagai inovasi awal dalam meningkatkan kualitas dan kemenarikan pembelajaran IPS pada materi sejarah Islam di kelas X.